Application of a new method to develop a CFD model to analyze wind characteristics for a complex terrain. (February 2020) - Sharma, Pramod Kumar; Warudkar, Vilas; Ahmed, Siraj
Abstract: The installation of an observation system on a complex terrain is necessary to predict accurate wind resource information for the successful setting up of a wind farm. Today, there is no Indian guideline exists to install an observation system for measuring the wind characteristics in a complex terrain wind farm. A wind characteristics analysis should be conducted, to determine land parameters such as roughness length, ruggedness index factor, and size of an inspection system; but, measuring in the field have found to be time-consuming and costly. The proposed research was carried at Jamgodrani hills, Near Dewas District (M.P.), India. The main aim of the work is to apply a new method using Sketchup and CREO 3.0 to develop a numerical computation computational fluid dynamics (CFD) model to forecast and analyze wind resource on a complex site. The filtered modeling file from CREO was further processed in ANSYS fluent to perform simulation. In the present study, a new technique was developed for terrain modeling using CFD. Further, the new model was validated using measured met mast data in complex terrain.